Protection of Unaccompanied Migrant Minors in Two European Union Countries: (Re)Acting) or Being (In)Different? - Carvalho,Maria Irene de (2023)
Abstract Although the European Union is a region of democratic values and social justice, with respect to the topic of unaccompanied migrant minors it remains an area of symbolic walls and borders between countries. Unaccompanied migrant minors and separated children are a risk group who enjoy recognised rights allowing for special protection, but such rights are not always acknowledged in practice. This article explores and analyses some of the main policies and national programmes for the protection of these minors in Italy and Portugal. Based on the relevant literature and legislation existing in these countries, this exploratory study critically highlights the pathways of protection and integration of unaccompanied migrant minors. Whereas the legal framework appears to focus mainly on the immediate basic needs, it is important to activate inclusive, consistent and durable policies that guarantee actual and holistic special protection to unaccompanied migrant minors.